Analisis Pendekatan Feminisme dalam Novel Wonder Women Rush Karya Septiana Nugraheni - Annisa Fitria (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to analyze aspects of feminism in the novel Wonder Women Rush by Septiana Nugraheni. The method used in this research is descriptive qualitative, with a feminist literary criticism approach. Data collection for this research was carried out by recording every data found in the novel Wonder Women by Septiana Nugraheni. Based on the results of data analysis, the following data was found. 1) Women are tough figures. 2) Women's independence in facing social pressure. 3) Women's multitasking ability. 4) Women's powerlessness against male power. 5) Women support other women. 6) Women must be brave in making decisions. This research emphasizes the need for awareness of the importance of gender equality and women's courage in making decisions for their own lives. This novel not only depicts individual struggles, but also reflects broader social dynamics related to women's emancipation. Therefore, the relationship between feminist theory and the novel